Produksi spora Bacillus thuringiensis pada media limbah dengan penambahan tepung cangkang keong mas dan toksisitasnya terhadap Spodoptera litura Fabr. (Lepidoptera:Noctuidae) - Yulia Pujiastuti; Triyansyah Triyansyah; Harman Hamidson; Effendy Effendy; Suparman Suparman (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2017)
Pujiastuti et al, 2017. Production of Bacillus thuringiensis Spores in Agricultural Waste with Addition of Golden Snail Shell Powder and its Toxicity Against Spodoptera litura Fabr. (Lepidoptera: Noctuidae). JLSO 6(2):150-157.Armyworm or Spodoptera litura is an important pest on the cultivation of plants. Controlling by using biological agents such as Bacillus thuringiensis is an alternative to the use of chemical insecticides which cause a negative impact on insects and environment. B. thuringiensis-based bio insecticide can be reproduced by using agricultural waste with the addition of golden snail shell flour. The study was aimed to investigate the production of B. thuringiensis spores on agricultural waste media and the addition of golden snail shell flour and its toxicity to armyworm, as well. The research design was a completely randomized design with 10 treatments and 3 replications. Treatment were the media of agricultural waste: 50 mL coconut water, 50 mL of tofu liquid waste, 50 mL of rice wash water and mixture of three media (v/v/v, 1:1:1) with the addition of golden shell flour as much as 5 g and mineral salt of CaCl2, MgSO4, K2HPO4, KH2PO4. The results showed the production of bacterial spores ranged from 8.90x107 spores/mL to 9.51x107 spores/mL with the highest production in the mixed treatment of the three waste media (coconut water, tofu waste and rice laundry water). In this treatment the level of toxicity was 40% in larvae of armyworm. The weight of leaf feed consumed by armyworm at various treatments was ranged from 36.33 to 46.67 g/10 larvae. The addition of mashed shell flour to growth media of B. thuringiensis did not increase the number of spores.